TIME-SAVERS: BERTRAM BROOKER AND THE POLITICS OF TIME AND MATERIAL CULTURE (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
The late writings and visual art of Bertram Brooker (1888-1955) represent an overlooked bridge between the space-time discourse of British modernist Wyndham Lewis and the Toronto School of Communication. The Canadian artist-advertiser’s multidisciplinary production of the 1930s through the mid-1950s revisits his earlier thematization of Bergsonian concepts of duration and “flux” in abstract canvases and articles for Marketingmagazine of the 1920s. Yet his illustrations for The Canadian Forum and the unpublished manuscript The Brave Voices (ca. 1953-55) reveal a fresh awareness of the limits of the Bergsonian paradigm as well as a deepening recognition of its implications as a critique of modernity following the stock market crash of 1929.